أثر السيولة والملاءة المالية والكفاءة الإدارية على ربحية شركات التأمين (دراسة تطبيقية على شركات التأمين السورية الخاصة) - الغصين, راغب; زاهر, لانا نبيل (Latakia University Journal - Economic and Legal Sciences Series, 2014)
هدفت هذه الدراسة إلى البحث عن احتمالية وجود علاقة بين نسب السيولة, والملاءة المالية, والكفاءة الإدارية, ونسب الربحية لشركات التأمين الخاصة خلال الفترة (2009-2013). وقامت الدراسة لتحقيق هذه الأهداف بالاعتماد على أساليب التحليل الإحصائي والمالي, حيث تمّ استخدام برنامج SPSS الإحصائي لتحليل البيانات. كما تمّ حساب التغيرات السنوية لكل نسبة من النسب المدروسة, بالإضافة إلى متوسط معدل التغير أو النمو خلال الفترة المدروسة, كما تم دراسة العلاقة بين كل من النسب المدروسة (السيولة, والملاءة المالية, والكفاءة الإدارية) وبين الربحية لمعرفة أثر كل من هذه النسب على الربحية, وذلك باستخدام الانحدار البسيط, ومن ثم تحديد النسبة الأكثر تأثيراً على الربحية باستخدام الانحدار المتعدد. وخلصت الدراسة إلى أن العلاقة مابين نسبة السيولة والربحية لشركات التأمين هي علاقة عكسية ومتينة جداً ودالة إحصائياً, وكانت العلاقة ما بين نسبة الملاءة المالية والربحية لشركات التأمين هي علاقة طردية ومتينة جداً ودالة إحصائياً, بينما كانت العلاقة ما بين نسبة الكفاءة الإدارية والربحية لشركات التأمين هي علاقة طردية ومتينة جداً ودالة إحصائياً. و كانت الملاءة المالية هي النسبة الأكثر تأثيراً في شركات التأمين. وهذا يؤكد على أن طبيعة العمل في شركات التأمين قائم على مبدأ العائد والمخاطرة. وأوصت الدراسة إلى تشجيع البحث العلمي في مجال التأمين, وتبني الدراسات العالمية المتعلقة بالتأمين, والعمل بالتنسيق مع الجامعات والمعاهد المتخصصة على إقامة الندوات, وعقد اللقاءات وتوزيع المنشورات لنشر الوعي التأميني. كما أوصت شركات التأمين بالعمل على تنويع استثماراتها بالإضافة إلى التخفيف من السياسة المتحفظة التي تتبعها. وأوصت إلى تفعيل الشراكة بين شركات التأمين والمصارف المحلية بالشكل الذي يسهم في تحقيق التنمية الاقتصادية والاجتماعية. This study tries to see if there is a possible relationship between liquidity, solvency as well as administrative efficiency and profitability ratios of private insurance companies during the period (2009-2013).The study tries to do so, using methods of statistical and financial analysis, particularly SPSS statistical software. Annual changes are calculated for each of the ratios studied, in addition to the average rate of change or growth during the period studied. The relationship between each of the ratios studied (liquidity, solvency, and administrative efficiency) and profitability is also analyzed to see the effect of each of these ratios on profitability, using simple regression. The most influential figure affecting profitability is then determined using multiple regression. The study concluds that the relationship between the ratio of liquidity and profitability of the insurance companies is an inverse relationship, very durable and statistically significant. The relationship between the ratio of the solvency and profitability of insurance companies is a positive relationship, very tough and statistically significant, while the relationship between ratio of administrative efficiency and profitability of insurance companies is a positive relationship, very strong and statistically significant. The solvency ratio is the most influential in the insurance companies. This confirms that the nature of the work in insurance companies is based on the principle of return and risk. The study recommends encouraging scientific research in the field of insurance, and the adoption of global studies related to insurance. It suggests work in coordination with universities and institutes to hold specialized seminars, meetings and distribute pamphlets to spread awareness of insurance. It also recommends that insurance companies work to diversify their investments and abandon conservative policies. The research also recommends activation of the partnership between the insurance companies and local banks as a way to contribute to achieving economic and social development.